MEMBACA DUNIA SUREALIS IBW. WIDIASA KENITEN DALAM KUMPULAN CERPEN BUDUH NGELAWANG - Juliana, I Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Buduh Ngelawang's short story collection is one of the literary works that was born from the hands of a teacher named IBW. Widiasa Keniten. Apart from being a teacher, he is also active in writing literary works in both Balinese and Indonesian. His works should be appreciated and given comments in order to add to the repertoire of literary criticism in the field of modern Balinese literature itself. In Buduh Ngelawang's short story collection, the author builds a new world in modern Balinese literature that has never been done before. The author offers a new model in structuring the modern Balinese literary form, namely the surreal form. On this occasion, Buduh Ngelawang's short story collection will be analyzed based on Tzevetan Todorov's narratological structure theory. In the narratological analysis, the semantics (in absensia) aspect will be discussed. The semantic aspect relates to the involvement of denotative meaning and connotative meaning as a way to express meaning.